Habitar o Provisório - Miranda, Bernardo Pizarro (Last 15 MIN, 2013)
'A profound change in our architectural conception of space has occurred during the last few decades No single practitioner, not any of us architects, is in a position to change the direction of evolution; it is new human relations, new social, economic, and technological conditions, that force our professional ideas in new directions, whether we will it or not'. G. Asplund, 1933